Akuntabilitas Pengelolaan Obat Rusak dan Kedaluwarsa Ditinjau dari Perspektif Akuntansi pada Puskesmas Sungai Apit - Mariani; Ardiansyah (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study discusses the recording and reporting of damaged and expired drugs at the Sungai Apit Health Center, Sungai Apit District, Siak Regency, Riau Province. Background of the Problem: Damaged and expired drugs are still found every year with a fairly large loss value. In 2023, the recorded loss due to damaged and expired drugs reached IDR 9,040,308, while in 2024 it increased to IDR 10,490,122. Novelty: This study is the initial basis for updating the reporting system for damaged and expired drugs at the Sungai Apit Health Center. Research Method: This study uses a descriptive quantitative method with a documentation and direct observation approach. Data are analyzed based on the value of losses due to damaged and expired drugs. Findings/Results: The results of the study indicate that although there was a decrease in the value of losses from 2022 to 2023, the recording and reporting system is still not optimal. Conclusion: This study concludes that a more modern, accurate, and efficient recording and reporting system is needed to reduce losses and support decision making in drug management in health centers